Comparative Study of Curriculum Management Models Between Islamic Educational Institutions and General Educational Institutions - Yulia, Fitri; Arizal, Jepri; Habibi; Wijaya, Candra; Hidayat, Rahmat; Azad, Inamul (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze the comparative curriculum management models between Islamic educational institutions and public educational institutions within the context of the national education system in Indonesia. The main focus of this study is to identify the similarities, differences, strengths, and weaknesses of the two curriculum management models. The research method used is a descriptive qualitative approach with literature review and observation of curriculum management practices in madrasas and public schools. The results show that both madrasas and public schools have curriculum management structures that follow national standards, but madrasas integrate Islamic religious values ​​into all aspects of learning. Madrasas tend to emphasize the spiritual, moral, and character dimensions of Islam through a curriculum based on the integration of religious and general knowledge. Meanwhile, public schools focus more on mastering academic competencies and practical skills as stipulated in the independent curriculum policy. The strength of madrasah curriculum management lies in the development of strong morals and religious values, while its weakness is limited innovation in the application of technology and contextual learning. In contrast, public schools excel in implementing adaptive learning models and digitalization, but face challenges in strengthening students' spiritual character. This study confirms that synergy between curriculum management models in madrasas and public schools can be an ideal solution for creating a holistic curriculum, balancing religious values ​​and academic competencies. Therefore, the results of this study are expected to serve as a reference for policymakers, educators, and curriculum developers in optimizing curriculum management that is relevant to the needs of the 21st century.